The Problem of the Value of Photography as a Document - Jakutovič, Sabina (Sensus Historiae, 2019)
The purpose of this article is to show the value of photography as a document. Photography is one of the forms of imaging the world. Photographic images are used to record and maintain the memory of the past. Unlike painting, photography accurately represents the world. Can we, for this reason, treat it as a direct source of knowledge about the past as a document?